Religious Moments as the Basis of Omni-Channel Marketing Communication Management at Prima Aqiqoh Bandar Lampung - Suharti, Bangun (PT. Riset Press International, 2025)
The livestock business is a unique business, different from ordinary businesses such as the daily necessities business. The livestock business is usually associated with special moments, namely Eid al-Adha (qurban) and aqiqoh. This business is very interesting to study, because this business is related to: special moments, special goods and services, as well as special market segmentation and target markets. The aqiqoh business is closely related to religious awareness as well as closely related to the economic capabilities of young Muslim families, when they decide to carry out aqiqoh. Similarly, the sale of livestock at the moment of Eid al-Adha, only occurs in a once-a-year period. Therefore, the livestock business requires marketing communication management that is managed specifically, different from other business marketing. This research method was conducted to obtain data through interviews, observations and documentation on the object of research. The purpose of this research is to find out how marketing management uses omni channels as a means of marketing livestock by utilizing religious moments, namely aqiqoh and qurban carried out by PT Prima Aqiqoh Lampung. The results of this study indicate that the combination of Instagram social media utilization and social networking is very effective for livestock business marketing media, especially at religious moments of aqiqoh and qurban.